Reflecting in/on field theory in practice - Grenfell, Michael (Tempo Social, 2018)
The article discuses the dimension of reflexivity within the work of the social theorist Pierre Bourdieu. It alludes to the provenance of Bourdieu’s theory of practice and the epistemology, which underpins it. Language is a key element in reflexivity, the article therefore outline’s Bourdieu approach to language and the significance it holds in the development of his key concepts, as well as the relationship between subject and object. Reference is made to the works of Habermas, Heidegger, Merleau-Ponty and others to offer a ground base in just what Bourdieusian reflexivity is and how it operates in practice. Phases and stages in methodology are referred to as well as how reflexivity should operate within them. Finally, the significance of the discussion is underlined with reference to consequent outcomes.